QCM Analysis for Two-Step Adsorption of Albumin and Fibronectin on Zirconia Surface - Masatsugu Hirota; Tohru Hayakawa (Advances in Materials Science and Engineering)
The adsorption of proteins on the dental implant surface is the first step in the key role of osseointegration. Many types of proteins exist in the living body and compete for adsorption on the material surface. As an implant material, partially stabilized zirconia (ZrO2) is currently an attractive alternative to titanium to overcome the shortcomings of titanium implants. In this study, we investigated the two-step adsorption of fibronectin (Fn) and bovine serum albumin (Alb) on the ZrO2 surface using a 27-MHz quartz crystal microbalance (QCM) method. A ZrO2 sensor was employed for the QCM measurements. Two-step adsorptions were performed as follows. (1) Fn-Alb series: first, the Fn solution was injected into the phosphate-buffered saline (PBS) solution, followed by the Alb solution. (2) Alb-Fn series: first, the Alb solution was injected, followed by the Fn solution. The decrease in frequency was monitored for 60 minutes after each protein injection. The adsorbed amounts of Fn or Alb were calculated by observing the decrease in frequency, and the apparent reaction rate, kobs, was obtained through the curve fitting of frequency shift against the adsorption time. No significant difference was observed in the adsorbed amounts of Fn and Alb between the Fn-Alb and Alb-Fn series (P>0.05). The kobs, rate of protein adsorption, in the second step was significantly slower than that in the first step for both Fn and Alb adsorption (P<0.05). There was no clear correlation between the amount of protein adsorbed on the ZrO2 sensor and the surface topography. It was concluded that the amount of protein adsorbed on the ZrO2 surface was not influenced by the two-step adsorption series, but the adsorption rate of proteins in the second step was affected by the first-step protein adsorption.